Peran Guru Terhadap Penggunan Pijar Sekolah pada Kelas X Mapel SKI di MAN 1 Ponorogo - Cahyani, Regita Cendikia; Jannah, Rin Nadatul; Saputra, Rizal Andika; Adawiyah, Robiatul; Mustofa, Roni Sahrul (Social Science Academic, 2024)
This research aims to analyze the role of teachers in using the Pijar Sekolah digital platform in learning the Islamic Cultural History (SKI) subject in class X MAN 1 Ponorogo. The method used in this research is descriptive qualitative with data collection techniques through observation, interviews and documentation. The research results show that teachers have a very important role in utilizing Pijar Sekolah as a learning medium. These roles include facilitator in guiding students in accessing learning materials, motivator in increasing students' interest in learning through digital media, and evaluator in assessing the effectiveness of using the platform. In addition, this research found that the use of Pijar Sekolah was able to increase student interactivity and involvement in the learning process, as well as facilitating access to more varied and up-to-date learning resources. In conclusion, the active role of teachers is very important in integrating digital technology in learning, and efforts to increase technological competence for teachers need to continue to be carried out to maximize the benefits of Pijar Sekolah in education.